Porcine Small Intestinal Submucosa Mesh for Treatment of Pelvic Organ Prolapsed - Ting-Ting Cao; Xiu-Li Sun; Shi-Yan Wang; Xin Yang; Jian-Liu Wang (Chinese Medical Journal, 2016)
Background: Pelvic organ prolapse (POP) is a major health concern that affects women. Surgeons have increasingly used prosthetic meshes to correct POP. However, the most common used is synthetic mesh, and absorbable mesh is less reported. This research aimed to evaluate the clinical effectiveness of porcine small intestinal submucosa (SIS). Methods: Consecutive forty POP patients who met the inclusion criteria underwent pelvic reconstruction surgery with SIS between March 2012 and December 2013. The patients' clinical characteristics were recorded preoperatively. Surgical outcomes, measured by objective and subjective success rates, were investigated. We evaluated the quality of life (QOL) using the Pelvic Floor Distress Inventory-20 (PFDI-20) and the Pelvic Floor Impact Questionnaire-7 (PFIQ-7). Sexual QOL was assessed by the Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire-12 (PISQ-12). Results: At postoperative 12 months, the subjective recurrence rate (7.5%) was much lower than the objective recurrence rate (40.0%). Postoperatively, no erosion was identified. One underwent a graft release procedure because of urinary retention, and one had anus sphincter reconstruction surgery due to defecation urgency. Another experienced posterior vaginal wall infection where the mesh was implanted, accompanied by severe vaginal pain. Estrogen cream relieved the pain. One patient with recurrence underwent a secondary surgery with Bard Mesh because of stage 3 anterior vaginal wall prolapse. Scoring system of PFDI-20 was from 59.150 ± 13.143 preoperatively to 8.400 ± 4.749 postoperatively and PFIQ-7 was from 73.350 ± 32.281 to 7.150 ± 3.110, while PISQ-12 was from 15.825 ± 4.050 to 12.725 ± 3.471. Conclusions: QOL and the degree of subjective satisfaction were significantly improved postoperatively. Anterior repair deserves more attention because of the higher recurrence rate. The long-term follow-up of the patient is warranted to draw firm conclusion.